Adverse event reporting of the IGF-1R monoclonal antibody teprotumumab: a real-world study based on the US food and drug administration adverse event reporting system - Zhao, Jiawei; Tao, Yong (Frontiers in Pharmacology, 2024)
Background: Teprotumumab, an IGF-1R monoclonal antibody, has shown significant efficacy in treating thyroid eye disease (TED). However, since teprotumumab was launched in 2020 and only approved in the United States, there were limited reports of post-marketing adverse events (AEs).In this study, we aimed to mine and analyze the AEs signals with teprotumumab on the basis of the United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) to provide instructions in clinical practice concerning adverse reactions and assistance in drug development and import/export into other countries.All AE reports were obtained from the FAERS database from the first quarter of 2020 to the fourth quarter of 2023. To comprehensively analyze the AEs, we applied four disproportionality analysis algorithms, including the reporting odds ratio (ROR), the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN), and the multi-item gamma Poisson shrinker (MGPS) algorithms.Results: A total of 687 reports from 200 patients related to administration of teprotumumab were obtained, and 78% of the cases was female. Signal detection of teprotumumab at the system organ class (SOC) level included gastrointestinal disorders, ear and labyrinth disorders, general disorders and administration site conditions, nervous system disorders, and musculoskeletal and connective tissue disorders. AEs that ranked top five at the preferred terms (PTs) level were muscle spasms, fatigue, tinnitus, headache, and deafness. The median time to those AEs onsets was 48 days (interquartile range 19.0-92.0 days) after administering drugs. Additionally, our results indicated the AEs in reproductive system and breast disorders because the prevalence of TED was more common in women.This study identified many AEs associated with teprotumumab and unveiled potential new AE signals. These results can provide valuable evidence for further clinical application of teprotumumab and are important in enhancing clinical medication safety.